Allelopathic potential of selected woody species growing on fly-ash deposits - Grbović, Filip; Gajić, Gordana; Branković, Snežana; Simić, Zoran; Ćirić, Andrija; Rakonjac, Ljubinko; Pavlović, Pavle; Topuzović, Marina (Archives of Biological Sciences, 2019)
Paper description: ● Phenolic compounds have the properties of allelochemicals that cause radicle growth inhibition of herbaceous plant species. ● Phenolic compounds, as potential allelochemicals derived from woody plant species growing on fly ash deposits, were investigated. ● The chemical characteristics of substrates in allelopathic plant relationships could be useful in understanding the impact of ecological factors on plant allelopathic activity as they influence invasive plants during initiation of the pedogenetic process of sterile substrate, such as fly ash. Abstract: The objective of this study was to determine the allelopathic potential of Robinia pseudoacacia L., Ailanthus altissima (Mill.) Swingle and Amorpha fruticosa L. that grow on the fly-ash deposits at the “Nikola Tesla – A” thermoelectric power plant in Obrenovac. The chemical characteristics of fly ash, such as pH, electrical conductivity (EC), content of carbon (C) and nitrogen (N), contents of available phosphorus (P2O5) and potassium (K2O), the contents of total and available Fe, Cu, Mn, Ni and Zn as well as of phenolic acids (3,5 dihydroxybenzoic acid (3,5-DHBA) and ferulic acid) and flavonoids (rutin and quercetin) were analyzed in control fly ash (bare zones without vegetation cover) and plant rhizospheric fly ash. In order to determine the allelopathic activity of phenolic compounds in fly ash, modified soil sandwich allelopathic biotests were performed, and Trifolium pratense L. (red clover) was used as the indicator species. A. fruticosa showed the highest allelopathic activity, followed by A. altissima whereas R. pseudoacacia showed the lowest allelopathic potential. Negative correlation was noted between radicle and hypocotyl growth inhibition of red clover and the pH of fly ash. Positive correlations were found between radicle growth inhibition and the content of C, P2O5, total concentrations of Cu, available concentrations of Mn and Ni, the contents of ferulic acid, 3,5-DHBA, and rutin. Our results indicate that A. fruticosa and A. altissima increased the content of phenolics in fly ash, which can act as allelochemicals leading to radicle growth inhibition of red clover in the pioneer plant community on fly-ash deposits. These woody species that colonized fly-ash deposits can initiate the beginning of pedogenetic processes altering the ecosystem processes at degraded sites. https://doi.org/10.2298/ABS180823050G Received: August 23, 2018; Revised: October 12, 2018; Accepted: October 17, 2018; Published online: November 7, 2018 How to cite this article: Grbović F, Gajić G, Branković S, Simić Z, Ćirić A, Rakonjac Lj, Pavlović P, Topuzović M. Allelopathic potential of selected woody species growing on fly-ash deposits. Arch Biol Sci. 2019;71(1):83-94.